2016
DOI: 10.1021/acs.inorgchem.6b00854
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effect of Axial Ligands on Easy-Plane Anisotropy of Pentagonal-Bipyramidal Cobalt(II) Single-Ion Magnets

Abstract: We herein reported the synthetic, structural, computational, and magnetic studies of four air-stable heptacoordinated mononuclear cobalt(II) complexes, namely, [Co(tdmmb)(HO)][BF] (1), [Co(tdmmb)(CN)]·2HO (2), [Co(tdmmb)(NCS)] (3), and [Co(tdmmb)(SPh)] (4) (tdmmb = 1,3,10,12-tetramethyl-1,2,11,12-tetraaza[[3](2,6)pyridino[3](2,9)-1,10-phenanthrolinophane-2,10-diene; SPh = thiophenol anion). Constrained by the rigid pentadentate macrocyclic ligand tdmmb, the Co centers in all of these complexes are in the hepta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 107 publications
5
60
0
Order By: Relevance
“…The complexes exhibit positive axial magnetic anisotropy (D) with non-zero rhombicity parameter ( Table 1). The sign and the magnitudes of D for 1-7 are in the range of previously reported those for the seven-coordinate pentagonal bipyramidal Co(II) complexes [24,25,33,34].…”
Section: Static Magnetic Measurementssupporting
confidence: 72%
See 1 more Smart Citation
“…The complexes exhibit positive axial magnetic anisotropy (D) with non-zero rhombicity parameter ( Table 1). The sign and the magnitudes of D for 1-7 are in the range of previously reported those for the seven-coordinate pentagonal bipyramidal Co(II) complexes [24,25,33,34].…”
Section: Static Magnetic Measurementssupporting
confidence: 72%
“…However, low coordinate complexes are not very stable which restricts their possible utility in different applications. At the same time, the experimental and theoretical studies of stable seven-coordinated metal centers with pentagonal bipyramidal geometry showed that such centers are highly promising as anisotropic spin carriers [16][17][18][19][20][21][22][23][24][25]. In this context, 3d-metallocomplexes with the pentadentate Schiff-base H 2 dapsc ligand (H 2 dapsc = 2,6-diacetylpyridine bis(semicarbazone), Figure 1) and its analogues are of considerable interest.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the magnetic anisotropy has been tuned by playing with donor/acceptor properties of two axial coligands, as was shown on series of Co II complexes, e.g. [Co(tdmmb)(X) 2 ] 2+/0 , where X = H 2 O, CN – , NCS – , SPh – , with the more pronounced anisotropy for the complex with SPh – ( D = 39.7 cm –1 ), or [Co(15‐pyN 3 O 2 )X 2 ], where X = Cl – , Br – and I – with the highest D = 41 cm –1 for the dibromido complex, and also on Mn II complexes [Mn(15‐pyN 3 O 2 )X], where X = Br – , I – , N 3 – , NCS – , with a small influence of axial coligands on the magnetic anisotropy (| D | < 0.7 cm –1 ).…”
Section: Introductionmentioning
confidence: 96%
“…geometry , . Nevertheless, several examples of linear (H 2 dabph) or macrocyclic ligands (15‐pydienN 3 O 2 , 15‐pydienN 5 , 15‐pyN 3 O 2 , tdmmb, or more recent TODA) (Figure S1) provided seven‐coordinate pentagonal bipyramidal complexes with a pentadentate ligand in the equatorial plane, which show a large easy‐axis magnetic anisotropy ( D < 0) in the case of Fe II and Ni II complexes, and on the other side, a large easy‐plane magnetic anisotropy ( D > 0) in the case of Co II complexes. Slow relaxation of magnetization was observed for [Fe(H 2 dabph)Cl 2 ] and [Fe(H 2 dabph‐NH 2 )Cl 2 ] ( τ 0 = 5 × 10 –9 s and U eff = 53 cm –1 ), for [{Ni(H 2 dabph)} 3 {W(CN) 8 } 2 ] (below the blocking temperature T N = 3.6 K, τ 0 = 1.6 × 10 –9 s, U eff = 30 K), and for many different Co II complexes , , , .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has been continuously focused on the single-ion magnetism of Co II ions with pentagonal bipyramidal (PBP) geometry, and we have reported a series of mononuclear complexes [20,21], as well as 1D and 2D coordination polymers based on the PBP Co II building blocks [8][9][10]. The influence of axial ligands and magnetic exchange interactions has been carefully studied in these systems.…”
Section: Introductionmentioning
confidence: 99%